Implementation of Bank Sharia Indonesia (BSI) Parepare KPR (House Ownership Credit) Products: - irwandi; Arifin, Asriadi; Adisaputra, Trian Fisman (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
AbstractThis paper aims to describe the implementation of mortgages by Bank Syariah Indonesia to meet the housing financing needs of customers with an installment system. This type of research is descriptive qualitative to explain in a narrative way the results of research that are more concrete and in-depth. The research approach used is phenomenological in nature. The target/subject of the research is the Parepare Branch of the BNI Syariah Bank which today has transformed into an Indonesian Sharia Bank. The research results were obtained from direct observation and interviews with informants. Data analysis techniques are research data collection, data reduction or data grouping, data compilation/display and drawing conclusions or research conclusions. The results of the study show that BNI Griya iB Hasanah is a consumer financing facility offered to finance customer housing loans (KPR) provided that the customer must have a fixed income. The stages that must be passed before financing is actually distributed to customers include SK requirements for prospective customers, salary slips, unit analysis, customer surveys, preparation of financing decisions, contract signing and determination of down payments.Keywords: KPR product; BNI Griya iB Hasanah; Bank Syariah Indonesia (BSI)AbstrakTulisan ini bertujuan untuk menggambarkan implementasi KPR oleh Bank Syariah Indonesia untuk memenuhi kebutuhan pembiayaan perumahan pada nasabah dengan system angsuran. Jenis penelitian ini adalah deskriptif kualitatif untuk menjelaskan secara naratif hasil penelitian yang lebih konkrit dan mendalam. Pendekatan penelitian yang digunakan bersifat fenomenologi. Target/Subjek penelitian adalah pihak Bank BNI Syariah Cabang Parepare yang hari ini telah bertransformasi menjadi Bank Syariah Indonesia. Hasil penelitian diperoleh dari observasi dan wawancara secara langsung kepada informan. Teknik analisis data adalah pengumpulan data penelitian, reduksi data atau pengelompokkan data, penyusunan/display data dan penarikan konklusi atau simpulan penelitian. Hasil penelitian menunjukkan bahwa BNI Griya iB Hasanah adalah fasilitas pembiayaan konsumtif yang ditawarkan dalam membiayai Kredit Pemilikan Rumah (KPR) nasabah dengan ketentuan bahwa nasabah tersebut harus memiliki pendapatan tetap (fix income). Tahapan yang harus dilalui sebelum pembiayaan benarbenar disalurkan kepada nasabah diantaranya adalah persyaratan SK calon nasabah, slip gaji, analisis unit, survey nasabah, penyusunan keputusan pembiayan, penandatangan akad dan penentuan uang muka.Kata kunci: Produk KPR; BNI Griya iB Hasanah; Bank Syariah Indonesia (BSI)